Association Between SARS-CoV-2 Vaccination and Development of Antinuclear Antibodies Among Students - Karol Laskowski; Justyna Paszkiewicz; Dorota Plewik; Adam Szepeluk; Kamil K. Hozyasz (SAGE Publishing, 2024)
Introduction: Antinuclear antibodies (ANA) are the hallmark of many connective tissue disorders (including lupus), which comprise roughly 5% to 10% of chronic debilitating diseases causing morbidity and mortality. In society, fear of these diseases increases illness-related uncertainty because the prognosis of progression is often difficult to determine and at least some symptoms fluctuate unpredictably. In the anti-vaccination movement, the question of the possible connection between vaccination and connective tissue disorders and other autoimmune diseases has grown to rank as an important argument for rejecting vaccination. In 2021, every fifth Polish first-degree nursing student decided to not be vaccinated against COVID-19. Objective: This study aimed to explore the prevalence of antinuclear antibodies in students vaccinated and unvaccinated against COVID-19. Participants and Methods: A single university cross-sectional study was performed in a small academic centre in Poland, where 210 students were recruited in 2022. All the participants were screened for SARS-CoV-2 IgG and antinuclear antibodies. Results: The mean age of the students who rejected vaccination was higher than that of those who were vaccinated. Among nursing students, 30.0% of vaccinated and 58.3% of unvaccinated individuals had COVID-19. The frequency of antinuclear antibodies was 3 times lower in vaccinated students than in unvaccinated students (2/159 vs 2/51; P  > .05). Conclusion: The results of our study did not confirm the rationality of rejecting vaccinations against COVID-19 for fear of developing autoimmune diseases among healthy students.